AI in journalism a case study on the sensemaking and sensegiving processes of local news organizations in Cebu - Araneta, Germine M.; Bernales, Chrys Chelsea S.; Tañongon, Crina E.; Velasquez, Mitchel P. (Cebu City College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
Technology continues to advance drastically over the past few years ? one of which is the emergence of Artificial Intelligence. While AI has been adopted in different fields, its usage has sparked concerns in journalism. Hence, this case study sought to know the current situation of AI use in CDN Digital and The Freeman and how these local news organizations make sense of this new technology and ethical concerns associated with its use. This study anchored on Karl Weick?s (1995) Sensemaking perspective and Gioia and Chittipeddi (1991) sensegiving concept to examine how organizations interpret AI as an ecological change and reduce its equivocality. Likewise, it explored how the organizational leaders' sensegiving process influences journalists? AI stance. Using semi-structured interviews and Braun and Clarke?s thematic analysis, the study revealed that CDN Digital and The Freeman have distinct approaches to AI. CDN Digital actively integrates AI but opposes its use in "ideation," while The Freeman declared non-use of AI and maintained traditional practices. Moreover, the study revealed that the management?s active sensegiving efforts have contributed to developing the news organization's unified AI stance, and the lack thereof has resulted in disconnected stance, thus apprehension among journalists remained.
Thesis (Bachelor of Arts in Communication)--UP Cebu, July 2024.
Includes bibliographical references and appendices.